The Impact of Living–Learning Program Scholarships on Scholarship Recipients. Issue 2 (15th March 2019) - Doyle, Jeff; Wheelis, Meaghann; Thompson, LaNette; Strietzel, Jeff
Abstract : Financial aid is often linked to evidence of learning inside the classroom (students' GPA) and financial need. This mixed-methods study describes an assessment of a scholarship designed to encourage learning outside the classroom that required incoming students to live in a living–learning community (LLC). Results showed that though receipt of the scholarship did not predict retention, it encouraged some students to live in an LLC where otherwise they might have chosen a different option.